2013
DOI: 10.1161/circheartfailure.112.000177
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor-γ Activation Prevents Sepsis-Related Cardiac Dysfunction and Mortality In Mice

Abstract: Background Cardiac dysfunction with sepsis is associated with both inflammation and reduced fatty acid oxidation (FAO). We hypothesized that energy deprivation accounts for sepsis-related cardiac dysfunction. Methods and Results E. coli lipopolysaccharide (LPS) administered to C57BL/6 mice (WT) induced cardiac dysfunction and reduced FAO and mRNA levels of peroxisome proliferator-activated receptor (PPAR) α and its downstream targets within 6-8h. Transgenic mice in which cardiomyocyte-specific expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
161
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 50 publications
14
161
2
Order By: Relevance
“…Furthermore, the NOX2 inhibitor apocynin prevents systolic dysfunction in vivo, but it does not cause a reduction in circulating proinflammatory cytokines or cardiac tissue inflammatory gene expression, demonstrating that cardiac contractility and systemic inflammation can be dissociated. This finding is consistent with our previous findings showing that induction of cardiac fatty acid oxidation and energy production improved cardiac function prior to alleviation of inflammation (11,13). These new findings, in combination with our prior work, suggest a crucial role for restoration of mitochondrial function and cardiac energetics as a way to maintain cardiac function in sepsis, independently of systemic inflammation, at least for the early stage of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the NOX2 inhibitor apocynin prevents systolic dysfunction in vivo, but it does not cause a reduction in circulating proinflammatory cytokines or cardiac tissue inflammatory gene expression, demonstrating that cardiac contractility and systemic inflammation can be dissociated. This finding is consistent with our previous findings showing that induction of cardiac fatty acid oxidation and energy production improved cardiac function prior to alleviation of inflammation (11,13). These new findings, in combination with our prior work, suggest a crucial role for restoration of mitochondrial function and cardiac energetics as a way to maintain cardiac function in sepsis, independently of systemic inflammation, at least for the early stage of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Samples were normalized against 18S ribosomal RNA. The sequences of the primers have been described previously (11).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PPARγ prevents severe RVF secondary to pulmonary arterial hypertension: Accumulating evidence has suggested that PPARγ agonist could protect the heart from adverse remodeling after ischemia injury, [16][17][18] which is mainly associated with left ventricular function. In order to distinguish the PPARγ protective effect on RV from LV and gain more insight into the protective effects related to PPARγ, echocardiographic and Doppler flow measurements were carried out for both RV and LV.…”
Section: Resultsmentioning
confidence: 99%